An Evaluation of the Biological Case for Design - Glass, David H. (Zygon, 2022)
Rope Kojonen has presented a novel argument for design in biology by drawing on insights from evolutionary science. Without objecting to the explanatory role of evolution, he argues that there is further explanatory work to be done and that this is best achieved by an appeal to design. Here, I interpret his argument, and attempt to evaluate it, as a conjunctive explanation since he appeals to two explanations to account for the purposeful order and complexity of living organisms. Understood in this way, I argue that he makes a very plausible case that two explanations (evolution and design) are better than one (evolution). I also explore the role that direct guidance by God might play in such an argument.